Screening practices, efficacy, safety and adherence to biologic therapies in a South African tertiary hospital - Ahmed, Mohammed Awad Eltoum; Scott, Christiaan; Gcelu, Ayanda; Steffen, Jonel; Isaacs, Thuraya; Hodkinson, Bridget (Frontiers in Musculoskeletal Disorders, 2023)
Introduction. The high cost and concern of adverse events, particularly infections, limit the use of biologic therapies. We undertook this retrospective study to document their use for immune-mediated diseases, and explore the screening practices, efficacy, safety, and adherence to bDMARDs in a tertiary hospital. Methods. A folder review of all adult and paediatric patients treated for IMDs with bDMARDs. Changes in disease activity were measured by disease-specific tools at 6, 12, 24-months and at the last available visit, and patient adherence to bDMARDs was explored by folder and pharmacy record review. Results. We studied 120 folders; 145 bDMARDs were prescribed (23 patients switched bDMARD). BDMARDs prescribed included tumour necrosis factor inhibitors (TNFi) (76), rituximab (54), tocilizumab (9), anakinra (3), abatacept (1), ustekinumab (1) and tofacitinib (1). The vast majority of patients had an excellent response and achieved low disease activity or remission at their last available visit. Adverse events included severe infection (9) including two cases of tuberculosis (TB), mild skin reaction (6) and severe infusion reactions (4). Therapy was discontinued in 13 patients, most commonly due to infection (5), lack of response (4), or poor adherence (3). Poor adherence was noted in 8/120 (6.7%). Complete latent TB infection screening was performed in only 35 patients (29.2%). Screening for Hepatitis B, C and HIV was performed in 28 (23.3%), 62 (51.7%) and 61 (50.8%) patients, respectively. Only 20.8% and 20.0% received the influenza and pneumococcal vaccination. Discussion and Conclusion. Biologic therapy was effective, and the most important serious adverse effect was infection, which was significantly associated with TNFi therapy. Vaccination and screening for TB, viral hepatitis and HIV was suboptimal. Of concern, poor adherence to bDMARDs was frequently encountered.